Production and function of Neolithic black-painted pottery from Schela Cladovei (Iron Gates, Romania) - Spataro, Michela (2020)
This paper presents for the first time the results of a combination of petrographic, geochemical and organic residue analyses of early Neolithic ceramics from the Iron Gates region of the Danube basin. Eleven early Neolithic potsherds from Schela Cladovei (Romania) were analysed in detail. The results of the petrographic analysis show that the ceramics were made with the same recipe that was used by Starčevo-Körös-Criș potters elsewhere in southeastern Europe. The SEM-EDX analysis shows one of the earliest uses of Mn-rich black pigments to decorate Neolithic European ceramics. Organic residue analyses detected dairy, non-ruminant and ruminant adipose fats. No evidence of aquatic resources was detected. In summary, the early Neolithic potters at the Iron Gates, although able to make coarse and more sophisticated painted ceramics, did not make specific vessels for a specific use.